Influence of Histology and Histomorphometry of Thigh Muscles on Thermal Stress-Related Physiological and Plasma Hormonal Responses in Three Broiler Strains - Haresh Kashinathrao Popalghat; Nrusingha Charan Behura; Lipismita Samal; Niranjan Sahoo; Umakanta Mishra; Susanta Kumar Dash; Abhijeet Champati; Soubhagya Muduli (Agricultural Research, 2025)

Comprehensive analysis of the major IgY antibody extraction strategies from chicken egg yolk - Dhruvi Patel; Gireesh Babu K.; Sreenivasa Nayaka; Amel Gacem; Pankaj Kumar; Apurva Sharma; Krishna Kumar Yadav; Lamjed Mansour; Haresh S. Kalasariya (Veterinary Immunology and Immunopathology, 2025)

Intensifying levulinic acid hydrogenation using mechanochemically prepared copper on manganese oxide catalysts - Nayan Jyoti Mazumdar; Praveen Kumar; Miryam Arredondo-Arechavala; Nancy Artioli; Haresh Manyar (Chemical Engineering Journal, 2023)

Total Interpretive Structural Modeling-Polarity (TISM-P) to analyze the impact of energy on the sustainability performance of hotels: a case study - Aarti Singh; Sushil; Haresh Kumar Sharma (Environment, Development and Sustainability, 2023)

Physiological and gene expression responses involved in teak (Tectona grandis L.) seedlings exposed to osmotic and salt stressors - Hemanshukumar J. Maisuria; Haresh L. Dhaduk; Sushil Kumar; Amar A. Sakure; Amarjeet S. Thounaojam (Molecular Biology Reports, 2023)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Heavy Metal Content of Suspended Particulate Matter at World’s Largest Ship-Breaking Yard, Alang-Sosiya, India - Shaik Basha; Premsingh Mansingh Gaur; Ravikumar Bhagwan Thorat; Rohitkumar Harikrishna Trivedi; Sandip Kumar Mukhopadhyay; Nisha Anand; Shalin Hemantbhai Desai; Kalpana Haresh Mody; Bhavnath Jha (Water, Air, & Soil Pollution, 2007)

Involvement of cyclooxygenase, phospholipase C and MAP kinase pathways in human platelet aggregation mediated by the synergistic interaction of adrenaline and PAF - Sheikh A. Saeed; Huma Rasheed; Zahra A. Hoodbhoy; Simeen R. Pasha; Zohair Mapara; Haresh Kumar; Bukhtiar H. Shah (Inflammopharmacology, 2001)

Effect of ultraviolet light on the dielectric behavior of bone at microwave frequencies - J. Behari; Haresh Kumar; R. Aruna (Annals of Biomedical Engineering, 1982)